Molecular and Clinical Overview of Type 1 Neurofibromatosis: Single Center Study and Mini Review on NF1-Associated Vasculopathy and Juvenile Myelomonocytic Leukemia - Şule Altıner; Alper Han Çebi (Gazi Medical Journal)
Objective: Neurofibromatosis type 1 (NF1) is a genetic disorder presenting primary with variable patterns of skin pigmentation, neurofibromas and iris Lisch nodules. In addition, likely pathogenic/pathogenic mutations of the NF1 gene predispose to multiple tumors. Juvenile myelomonocytic leukemia (JMML) is also associated with NF1. Molecular diagnosis is important in patients with an atypical presentation, as well as in children who have not yet developed sufficient characteristic features or for providing prenatal diagnosis. The purpose of this study was to define NF1 gene mutations in the northeastern part of Türkiye and to contribute to the mutational spectrum of NF1. In addition, rare findings, such as cerebral vasculopathy and JMML, were discussed over the phenotypic findings. Methods: In this study, NF1 gene sequence analysis was performed using next-generation sequencing in 32 unrelated Turkish patients with a prediagnosis of NF1. Results: Disease-causing variants were found in 68.75% (n=22/32) of the patients, whereas two of them were novel. Our study was also important in the aspect of vasculopathy regarding the frequency which was 9.1% of in a relatively small patient group. Another aspect was the distinct distribution of malignant tumors. In contrast to central nervous system malignancies, which are the most common malignancies apart from malignant peripheral nerve sheath tumors in the literature, JMML was the most common in our study. Conclusion: The aim of this study is to draw attention to rare symptoms, such as vasculopathy and JMML, in NF1 in a small cohort. Although JMML is a rare childhood cancer, it is accompanied by RASopathies. It is important to investigate this association because JMLL treatment approaches change in the presence of germline mutations.